PERLINDUNGAN PEMILIK MEREK PERTAMA PADA SISTEM KONSTITUTIF - Arfi Dyah Chatarina (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2019)
With a brand, the company that produces the goods will be easily recognized. When the brand is already known by the public, will raise the reputation of the brand of the product so that in the event of violations, such as piracy or imitation famous brand are harmed is the first legitimate brand owners. Based on the permaslaah, then this article will be discussed about the protection of brand owners in the legal system of the first brand in Indonesia. Based on the background of the above can be identified several problems that include (1) the protection of brands based on the works of the law, system theory (2) system registration brand in Indonesia from time to time in accordance with the act of the brand that once existed in the Indonesia, (3) the protection of the law on the registration of the first brand owner brand with constitutive system, (4) a system of registration of the trademark in other countries. To address these problems, the authors use the juridical normative research methods. The system of registration, a brand under law 20/2016 about brands and geographical indications has a first to file. Legal protection of trademark owners first can be divided into two, namely the preventive legal protection that is made through registration of the brand and the repressive nature of legal protection that is done in case of violation of the brand through lawsuits or criminal charges. In addition, the act 20/2016 about brands and geographical indications as well arrange regarding the protection of brand owners first through temporary assignment court to protect its brand in order to prevent a greater harm. System registration brand in Malaysia with the same registration system brand in Indonesia. The two countries adhere to the basic constitutive system with first to file, i.e. the first applicant is a legitimate brand owners and obtained exclusive rights over its brand.